Retrospective view and thematic analysis of value co-creation through bibliometric analysis. (19th May 2022) - Hassan Shah, Syed Hamad; Noor, Saleha; Bayiz Ahmad, Ahmad; Saleem Butt, Atif; Lei, Shen
Abstract : Value co-creation (VCC) is an emerging phenomenon in the business eco-system that has received scholars' attention over the past decade. This study explored most influential journals, institutions, countries and different research themes of VCC publications through bibliometric analysis. These publications were retrieved from Web of Science (WoS) and bibliometric analysis was conducted by VOSviewer. Our analysis shows that Industrial marketing management was the most productive journal in VCC publications. The USA, England and China ranked first, second and third in terms of total publications (TP) but there was a huge difference in terms of citations. Karlstad and Sydney Universities were the most productive institutions with respect to TP and citations respectively. Moreover, most influential countries and institutions (citing the same publications) were grouped through a bibliographic coupling. Five themes have been emerged outlining the explicit role of VCC in (1) sustainability, open innovation, sharing economy (2) customer participation and service quality (3) service science and resource integration (4) eco-system and social media (5) value co-destruction. This may be the first bibliometric study to explore the thematic analysis of VCC publications at a glance and researchers as well as students may find out the current status and potential research gaps of VCC research.